The key drivers of commercial banks profitability in a subdued Zimbabwean economy – Lessons for the sector - Chipunza, R (My University, 2023)
The study was hinged upon analysing the impact of the key drivers of the banking sector’s phenomenal performance despite operating in a subdued Zimbabwean economy for the period from 2016 to 2022. The available literature on the key drivers of commercial banks' profitability in a subdued Zimbabwean economy focuses on understanding the factors that influence the financial performance of banks in such an economic environment. However, there are knowledge gaps in the current scholarly discourse that need to be addressed to enhance the understanding of the drivers of bank profitability in Zimbabwe hence the research. The researcher collected and analysed data from active 14 commercial banks in Zimbabwe. Correlational analysis statistical tests were performed on the gathered data in order to investigate the hypotheses presented. In addition, a pooled regression model was built from data collected from proxies of hypothetical key drivers which included Return on Assets (ROA), Digitisation, Net Interest Margin, Non-interest Income, Quality of Assets, Capital Adequacy and Management Efficiency. The information was compiled from business annual reports covering the 2016–2022 timeframe. The researcher entered these averages into Eviews 12.0 for statistical regression and association analysis after obtaining them from Microsoft Excel. The findings of the regression analysis suggest that Capital Adequacy and Management Efficiency have a significant positive effect on commercial banks' profitability in a subdued Zimbabwean economy, while Digitization, Non-interest Income and Quality of Assets do not have a statistically significant effect.
Keywords: key drivers; banking; commercial bank; HUMANITIES and RELIGION::History and philosophy subjects::History subjects::Economic history